Implementation of SSI-Based PBL Model to Develop Students' Critical Thinking Skills in Science Learning - Febrianty, Riana; Az Zahra, Firda; Lestari, Tuti; Arif, Khairil (Pendidikan IPA, FMIPA, UNP, 2025)
Critical thinking is one of the most essential skills to be developed in 21st-century education. However, many classroom activities still rely on conventional methods that fail to actively engage students. This study aimed to investigate the effect of integrating the Problem-Based Learning (PBL) model with Socio-Scientific Issues (SSI) on junior high school students’ critical thinking skills in the topics of ecology and biodiversity. A quasi-experimental method with a non-equivalent control group design was employed. The research subjects consisted of two eighth-grade classes at SMP Negeri 35 Padang: one class implemented the PBL-SSI model as the experimental group, while the other used conventional learning as the control group. Data were collected through pre-tests and post-tests and analyzed using the t-test. The results showed that before the intervention, students in both groups had comparable levels of critical thinking skills. However, after the intervention, the experimental group demonstrated a significant improvement (tcount = 7.234 > ttable = 2.005). Improvements were evident across six indicators of critical thinking, including information analysis, drawing conclusions, and evaluation. These findings indicate that the PBL-SSI model effectively enhances students’ critical thinking skills through meaningful, contextual, and applicable learning experiences. By incorporating real-life issues, this model encourages active student participation in discussion, problem-solving, and decision-making, thereby making the learning process more engaging and meaningful.